1995
DOI: 10.1159/000126840
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Administration of Human Corticotropin-Releasing Hormone in the Absence of Glucocorticoid Feedback in Man

Abstract: Continuous 24-hour infusions of a maximally stimulating dose (1 µg/kg/h) of corticotropin-releasing hormone (CRH) have been shown to cause elevations of plasma cortisol and ACTH, but the pattern of results were confounded by serum cortisol causing feedback changes. We have looked at ACTH responses to saline or CRH infusions over 24 h in 6 normal subjects who, in addition, received either placebo or metyrapone, an 11β-hydroxylase inhibitor which blocks the formation of cortisol and thus abolishes glucocorticoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Further study on single neuronal activity in the SCN revealed that the dorsomedial part of the SCN is an intrinsic oscillating pacemaker [37], Additionally, the dorsomedial part of SCN is also the main location of AVP neurons [12]. Moreover, the circadian rhythm persists despite a continuous infusion of CRH [38] or AVP, suggesting that CRH or AVP alone is not the mediator of ACTH pulses. Actually, a study discovered a circadian rhythm in AVP RNA expression and the loss of the circadian rhythm of AVP RNA expression was shown in the transgenic CLOCK knockout mice [13].…”
Section: Discussionmentioning
confidence: 99%
“…Further study on single neuronal activity in the SCN revealed that the dorsomedial part of the SCN is an intrinsic oscillating pacemaker [37], Additionally, the dorsomedial part of SCN is also the main location of AVP neurons [12]. Moreover, the circadian rhythm persists despite a continuous infusion of CRH [38] or AVP, suggesting that CRH or AVP alone is not the mediator of ACTH pulses. Actually, a study discovered a circadian rhythm in AVP RNA expression and the loss of the circadian rhythm of AVP RNA expression was shown in the transgenic CLOCK knockout mice [13].…”
Section: Discussionmentioning
confidence: 99%
“…A role for vasopressin release from the PVN in the control of rhythmic ACTH release has been suggested by human experiments where negative feedback regulation by GCs was eliminated by metyrapone treatment and CRH was infused iv at a constant rate. Under these conditions, a clear 24-hour rhythm of ACTH was observed, but it was set at a higher mean level due to the absence of negative feedback ( 130 ). High-affinity MRs in limbic structures, such as the hippocampus, mediate the effect of GCs on the maintenance of basal activity in the HPA axis at that nadir time (late evening in humans, early morning in nocturnal rodents).…”
Section: The Circadian Rhythmicity Of Glucocorticoid Releasementioning
confidence: 99%
“…Our findings open perspectives for novel strategies to protect long-stay ICU patients against the risk of developing adrenal insufficiency. If the lack of priming of the corticotropes by CRH would be responsible for reduced ACTH expression and secretion, providing CRH could potentially allow (re)activation of ACTH synthesis and release in response to any fall in cortisol and could hereby prevent adrenal atrophy in the prolonged phase of illness [ 45 ]. It has been shown that continuous infusion of CRH can reactivate ACTH secretion with preservation of circadian rhythmicity and pulsatility [ 46 ].…”
Section: Discussionmentioning
confidence: 99%